A Custom Ultra-Low-Cost 3D Bioprinter Supports Cell Growth and Differentiation - Ioannidis, Konstantinos; Danalatos, Rodolfos I.; Champeris Tsaniras, Spyridon; Kaplani, Konstantina; Lokka, Georgia; Kanellou, Anastasia; Papachristou, Dionysios J.; Bokias, Georgios; Lygerou, Zoi; Taraviras, Stavros (Frontiers in Bioengineering and Biotechnology, 2020)
Advances in 3D bioprinting have allowed the use of stem cells along with biomaterials and growth factors towards novel tissue engineering approaches. However, the cost of these systems along with their consumables is currently extremely high, limiting their applicability. To address this, we converted a 3D printer into an opensource 3D bioprinter and produced a customized bioink based on accessible alginate/gelatin precursors, leading to a cost-effective solution. The bioprinter’s resolution, including line width, spreading ratio and extrusion uniformity measurements, along with the rheological properties of the bioinks were analyzed, revealing high bioprinting accuracy within the printability window. Following the bioprinting process, cell survival and proliferation were validated on HeLa Kyoto and HEK293T cell lines. In addition, we isolated and 3D bioprinted postnatal neural stem cell progenitors derived from the mouse subventricular zone as well as mesenchymal stem cells derived from mouse bone marrow. Our results suggest that our low-cost 3D bioprinter can support cell proliferation and differentiation of two different types of primary stem cell populations, indicating that it can be used as a reliable tool for developing efficient research models for stem cell research and tissue engineering.